2016
DOI: 10.1123/pes.2015-0212
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Construct Validity of Yo-Yo Tests in Untrained and Soccer-Trained Schoolgirls Aged 9–16

Abstract: The Yo-Yo tests are reliable for determining intermittent-exercise capacity and %HRpeak for soccer players and untrained 9- to 16-year-old girls. They also possess construct validity with better performances for soccer players compared with untrained age-matched girls, despite similar %HRpeak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 28 publications
1
45
3
Order By: Relevance
“…The aim of this study was to examine the capability of different field and laboratory testing protocols, as well as small‐sided football games (7v7), to induce exercise HR max in recreational football players. A treadmill testing protocol for VO 2max assessment and popular football‐specific field tests commonly suggested as valid, reliable, and feasible procedures for assessing HR max were considered . Additionally, exercise HR was monitored during small‐sided recreational football matches in order to explore the nature of HR peak values during casual intermittent exercise .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this study was to examine the capability of different field and laboratory testing protocols, as well as small‐sided football games (7v7), to induce exercise HR max in recreational football players. A treadmill testing protocol for VO 2max assessment and popular football‐specific field tests commonly suggested as valid, reliable, and feasible procedures for assessing HR max were considered . Additionally, exercise HR was monitored during small‐sided recreational football matches in order to explore the nature of HR peak values during casual intermittent exercise .…”
Section: Discussionmentioning
confidence: 99%
“…A suggested practical alternative to laboratory treadmill protocols is endurance field testing . The Yo‐Yo intermittent tests, in their different versions and levels, are proposed as feasible, valid, and reliable field‐testing protocols for assessing HR max in football players across different competitive levels, ages, and genders under field conditions, being very popular in this sport …”
Section: Introductionmentioning
confidence: 99%
“…For the YYIE1, CV of 5.7% was observed in young soccer players (age ~14, n = 51) (Wong et al, 2011) and for the YYIE2, CV of 4.5% was observed in domestic female soccer players ( n = 27) (Bradley et al, 2014). With respect to age (and potentially training experience in intermittent sports) as a major confounding factor for test reproducibility, Póvoas et al reported on Yo-Yo tests in schoolboys (9–16 years) and observed that the CV decreased with increasing age from 11.1 to 8.5% (Póvoas et al, 2016). Deprez and colleagues reported that the CV for the YYIR1 decreased with increasing age from 17.3 to 7.9% in 78 sub- and non-elite soccer players (age-range 11.3–17.2 years) (Deprez et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, direct assessment of VO 2max in laboratory or field conditions requires the use of standard ergometers and portable gas analyzers, which may be inaccessible for most recreational football players. Maximal endurance field tests may represent a valid alternative to laboratory tests for aerobic fitness assessment . However, since participant's effort to exhaustion is required in maximal tests, their recurrent use for health and for motivation issues may be discouraged, especially in health‐related exercise interventions …”
Section: Introductionmentioning
confidence: 99%
“…Their maximal nature discourages the use of YYIE1 and 2 for repeated estimation of players’ aerobic fitness in order to optimize training implementation (ie, training intensity and or volume/density) . This is in spite of the proven validity and reliability of the YYIE1 and 2 tests across different populations . Thus, submaximal versions were proposed for estimating aerobic fitness level at baseline and during training interventions, when repeated use is required .…”
Section: Introductionmentioning
confidence: 99%